Perancangan Sistem Informasi Pelayanan Jasa Laundry Berbasis Web Dengan Digital Prototyping Design - Samodro, Heronimus Riski; Rudianto, Christ (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Pas Laundry is a business engaged in laundry services located in Salatiga City. Currently, the service process and record-keeping are still carried out manually, where customers come in and Pas Laundry only provides an estimated completion time of 3 days, which can be longer due to a high volume of queues. The research objective at PAS Laundry is to design a web-based information system that customers can use to view laundry status and assist in transaction management recording to facilitate transaction recording activities. Due to the large number of customers using laundry services, this laundry business is overwhelmed with recording tasks, such as the incorrect conveyance of information about the duration of the laundry process and errors in calculating the laundry costs that should be paid by customers. Therefore, this research discusses laundry service using a qualitative method, where the data used is obtained from interviews with relevant informants and direct observations at PAS Laundry. The results of this research are expected to help customers in viewing laundry status and assist employees in recording transactions between customers and PAS Laundry to avoid errors in recording.